Neo-Gramscian perspectives on international communication: China’s hegemony and Indonesia’s counter-diplomacy in Southeast Asia - Khoirunnisa Khoirunnisa; Arief Subhan; Ridzki Rinanto Sigit; Prasetya Yoga Santoso; Didi Jubaidi (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
China’s growing influence in Southeast Asia has increasingly been exercised not only through material power, but also through international communication and discursive practices that shape regional norms and perceptions. Existing studies on China’s rise tend to privilege economic and strategic explanations, often overlooking the communicative processes through which hegemony is constructed and legitimized. Addressing this gap, this article examines China’s regional influence from a neo-Gramscian perspective, focusing on international communication as an arena of hegemonic consolidation and contestation. This study aims to analyze how China articulates hegemonic narratives in Southeast Asia and how Indonesia responds through communication-based counter-diplomacy. Using a qualitative case study approach, this study analyzes secondary data consisting of policy documents, diplomatic statements, media coverage, and digital diplomacy materials published between 2014 and 2024. The data are examined through discourse analysis, framing analysis, and qualitative content analysis to identify patterns of hegemonic narratives and counter-narratives. The findings show that China’s hegemony operates through the integration of material initiatives such as the Belt and Road Initiative and the Global Security Initiative—with discursive strategies that normalize Chinese leadership. Indonesia responds through adaptive counter-diplomacy that emphasizes international communication, ASEAN centrality, and inclusive regional norms to preserve narrative autonomy under conditions of asymmetric interdependence. The study demonstrates that counter-hegemonic practices in contemporary regional politics increasingly rely on communicative and symbolic strategies rather than overt confrontation.